DETERMINANTS OF INDONESIAN COFFEE EXPORTS TO THE TOP FIVE DESTINATION COUNTRIES - Andika Emgita Tarigan; Ida Ayu Meisthya Pratiwi (Adisam Publisher, 2026)
Coffee is one of Indonesia’s leading plantation commodities, playing a vital role in international trade and contributing significantly to national foreign exchange earnings. Although Indonesia is among the world’s largest coffee producers, with production reaching approximately 760 thousand tons in 2023, its export performance remains suboptimal, with only about 36% of total production exported. This indicates a gap between production capacity and export realization, as well as reflecting stagnation in coffee export growth over the past few decades. This study aims to analyze the effects of international coffee prices, import tariffs, the exchange rate of the Indonesian rupiah against the United States dollar, and the real Gross Domestic Product (GDP) of destination countries on Indonesia’s coffee exports to five major destination countries, namely the United States, Japan, Germany, Italy, and Malaysia, during the 2003–2024 period. This research employs a quantitative approach using panel data analysis and the Random Effect Model (REM) estimation method, selected based on the Chow test and Hausman test. The results indicate that the GDP of destination countries has a positive and significant effect on Indonesia’s coffee exports, while the exchange rate has a negative and significant effect. Meanwhile, international coffee prices and import tariffs do not have a significant effect on Indonesia’s coffee exports.